Caesarean Section: Mortality and Morbidity - Mamta Gupta (Journal of Clinical and Diagnostic Research, 2018)
Caesarean Section (CS) is the most common obstetric surgery performed today. With advancement of anaesthesia and technique resulting in improved outcome and safety, its rate has been rising. Nevertheless, it carries risk of complications resulting in morbidity and sometimes mortality. Therefore, CSs done without medial indications, remains questionable. Maternal mortality and morbidity after caesarean birth is nearly five times than vaginal births, especially the risks of haemorrhage, sepsis, thromboembolism and amniotic fluid embolism. In a subsequent pregnancy, CS increases the risks of placenta previa and adherent placenta which may further result in higher risk of haemorrhage and peripartum hysterectomy. Technical difficulties due to adhesions increase the risk of injury to bladder and bowel. Though CS can be life saving for a foetus in jeopardy, yet in countries with high caesarean rate increased neonatal mortality and morbidity is seen i.e., iatrogenic pre-term births and respiratory morbidity. Risk of rupture uterus and stillbirths in women with previous CS also increase perinatal mortality. Neonatal adaptations is delayed in caesarean babies i.e., maintenance of body temperature, glycaemia and pulmonary respiration. Development of neonatal immune system is also affected in babies born by CS. Hence, CS should be done only if medically indicated.